A reafirmação do bairro:um estudo geo-histórico do bairro do Alecrim na cidade de Natal-RN - Bezerra, Josué Alencar (2005)
By the end of the 21st Century, economy globalization trends to show a velocity process through which market being expanded characterized by an intense going on of the internationalization of finance, after that marginalizing the periphery of the social spaces. It is clear to see that this process occurred in those less developed countries happens in an accentuated way just because income distribution that is so regressive and also because the insufficient enclosing of the social programs, we find this situation in a big part of Brazilian cities. The marginalizing social economical process observed in Natal, a city located in the east coast part of Northeast region in Brazil and that owns a population upper to 778 thousand in habitants is nearly linked to the extension of goods and services commerce. The installation of new urban activities in the city pointed out tourist activity as the greater impulsive thing in the phenomenon promotion, most of them aiming to promote Natal to the national and international scenery. It privilege strongly in the South zone with economical implementations such as shopping s centers, supermarkets, and home buildings condominiums leading to a loss of functionality of some traditional district located in central areas of the city. Notwithstanding, some spaces, for instance Alecrim district officially created in 1911, has notably resisted to the expansion of the urban process pointed out in Natal in the last years. So that this put Alecrim District as a district with originally characteristics reaffirmed along the historical process form old times. The predominance of some residential characteristics such as the incidence of some villages and a concentration of a big and confuse popular commerce distributed along streets puts Alecrim District as a resistant space in Natal. The same way analyze Alecrim District under the prism of Historic Geography because we understand this way it accomplishes a fundamental role in the theoretical methodological development of our work, just when we analyze the time as a variant in our object of study. It is still inside this theoretical field that we carry out a brief reviewing about quarter/district definition, under the optic from several registered and scientific resources taken into account along this work, because we understand that it was necessary to think this important spatial unit especially to know exactly what we are referring to as a district and so we can reaffirm Alecrim as an important and traditional district to Natal and it has been resisting to spatial transformation verified in the last years in Natal city. To give support to our reflection we used methodological tools related to inhabitants lifestyles knowledge and also the study of Alecrim District as a space that promote a certain centrality in Natal as some indicators to keep original characteristics in the district in Natal